ASSESSING EFFICACIES OF INSECT PEST MANAGEMENT METHODS TO PRESERVE NUTRITIONAL COMPOSITION OF BAGGED MAIZE IN STOREHOUSES LOCATED IN MARKETS IN NIGERIA (2021)
Maize needs to be stored using effective and safe postharvest management measures to prevent physical insect damage as well as ensure stability of nutritional quality during storage. In this study, conducted in February-December 2016, insect pest management methods for bagged maize preservation in storehouses located in markets in Nigeria were evaluated for their ability to preserve nutritional quality. Study locations were :n three grain markets, namely Eleekara market in Oyo town and Arisekola market i ' Ibadan, Oyo State, South West Nigeria, and Ago market in Ilorin, Kwara State, North Central Nigeria. Treatments comprised Piper guineense (Botanical), Bularf diatomaceous earth (DE), permethrin powder (Rambo™) (Permethrin), PICS bags (hermetic) and ZeroFly® bags (non-hermetic). The study also had negative control (Control) comprising untreated maize in polypropylene bags. In geeras a result of insect infestation, protein content increased in all treatments except KCS which had the least infestation. After 11 months of storage, Permethrin and PICS treatments had the lowest insect infestation levels and the highest energy levels. Energy level in the Botanical treatment was also high and similar to levels in Permethrin and PICS treatments most likely due to fats and essential oils in P. guineense being adsorbed and/or absorbed by kernels. Fat content was lower in the Control and DE treatments likely due to the Control having the highest insect infestation and the DE adsorbing and/or absorbing fat from kernels. During stor g„ carbohydrate content decreased in all treatments except the Control. However, even in the Control, there was a clear trend of decrease in carbohydrate content. Because the Control had the highest insect (Sitophilus zeamais) infestation and insect damaged kernels (IDK), this trend in decrease in carbohydrate content may be insect related. Ash content increased in the ZeroFly treatment, was unchanged in Botanical, Control, and PICS treatments, and decreased in DE and Permethrin treatments. Nutritional quality variables in this study were within or close to known value ranges for maize. Therefore, use of maize that had been fumigated well and had a relatively low initial grain MC (9.1%), in addition to the effects of the treatments most likely slowed down population growth of the several insect r pe^es that were found and contributed to preserving nutritional quality. The relatively low insect populations in all treatments, including the Control, during the February-September period probably reduced the clarity of effects of infestation on nutriti nal composition reported in this study.